2010
DOI: 10.1016/j.physleta.2010.09.050
|View full text |Cite
|
Sign up to set email alerts
|

Jamming in complex networks with degree correlation

Abstract: We study the effects of the degree-degree correlations on the pressure congestion J when we apply a dynamical process on scale free complex networks using the gradient network approach. We find that the pressure congestion for disassortative (assortative) networks is lower (bigger) than the one for uncorrelated networks which allow us to affirm that disassortative networks enhance transport through them. This result agree with the fact that many real world transportation networks naturally evolve to this kind … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…When r = 0 the network is uncorrelated. As observed in many other works the degree-degree correlation affects considerably the processes that occur on top of them [13][14][15].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…When r = 0 the network is uncorrelated. As observed in many other works the degree-degree correlation affects considerably the processes that occur on top of them [13][14][15].…”
Section: Introductionmentioning
confidence: 80%
“…The optimal synchronization found for assortative networks is in our model a topological effect due to the correlations. This is an unexpected result because in many researches it was found that disassortative networks (communication networks) are better for transport [14] and to synchronize oscillators [15]. 0.335 (r min ) (⋄).…”
Section: Discussionmentioning
confidence: 99%
“…A disassortative network structure is relatively scattered, core nodes tend to connect with non-core nodes, and there are likely to be more connections in the network, which affects the network's recovery. In this study, the Pearson correlation coefficient method is used to quantify the assortativity of the network by calculating the joint probability distribution of the nodes at both ends of any edge in the network [53]. The formula is as in ( 13):…”
Section: B) Evaluation Of Network Recoverymentioning
confidence: 99%
“…In biological and technological networks, high-degree nodes often preferably connect to low-degree nodes, which is referred to as -dissassortative mixing‖. The degree correlation has important influence on the topological properties of networks and may impact related problems on networks such as stability [6], the robustness of networks against attacks [7], the network controllability [8], the traffic dynamics on networks [9,10], the network synchronization [11][12][13], the spreading of information or infections and other dynamic processes [7,[13][14][15][16][17][18][19][20][21][22][23][24].In order to characterize and understand such preference of connections in complex networks, many statistical measures and network models have been introduced and investigated [2,3,[25][26][27][28][29][30][31][32][33][34][35][36]. For example, the average nearest neighbors' degree of nodes (ANND) [3] and the degree correlation coefficient…”
mentioning
confidence: 99%